Syntactical Analysis of Students’ Writing Error (ELATICS JOURNAL, 2024)
This analysis examines the various types of grammatical errors found in a set of sentences, with the goal of assessing the writer's proficiency in constructing proper English sentence structure and syntax. The errors identified include incomplete sentences/sentence fragments, subject-verb agreement issues, missing verbs, redundant or incorrect verb usage, pronoun usage errors, and problems with missing words and improper word order. A detailed examination of these error types from a syntactical perspective reveals a fundamental lack of understanding of the basic components and rules required for building grammatically correct sentences in English. The incomplete sentences and sentence fragments indicate a deficiency in applying the subject-verb-object structure, while the subject-verb agreement issues, missing verbs, and improper verb usage point to gaps in comprehending verb conjugation and incorporation within the sentence. Additionally, the pronoun usage errors demonstrate a lack of knowledge about anaphoric reference, and the missing words and incorrect word order reveal a poor grasp of the relationships between sentence elements. Collectively, these findings lead to the conclusion that the writer has a deep-seated problem with mastering English grammar and syntax at the most fundamental level, and significant remedial work would be required to strengthen their foundational knowledge and application of these core linguistic principles, with targeted instruction and practice in sentence structure and syntax being essential for improving their written and verbal communication skills.